Development Of Human Resource Quality Through The Application Of Performance Management System at KPPBC TMP A Bogor - Akbar, Muhammad; Muhammad Nur Abdi (Citakonsultindo, 2025)
This research examines the role of performance management in improving the quality of human resources and organizational effectiveness in the Treasury Section of the Supervision and Service Office of Customs and Excise Type Madya Pabean A Bogor (KPPBC TMP A Bogor). The study focuses on how the performance management system, including performance planning through Performance Agreements (PK) and Employee Performance Targets (SKP), individual performance dialogue, periodic monitoring, and evaluation based on measurable indicators, is implemented and contributes to increasing accountability, work coordination, and achievement of organizational targets. The research uses a descriptive qualitative approach based on literature studies analyzed through policy documents, internal reports, and Ministry of Finance regulations. The results show that the performance management system is able to clarify work expectations, strengthen collaboration, and improve the quality of business processes in the Treasury Section. In addition, the application of the system impacts the increasing competence of employees, a more adaptive work culture, and alignment between individual performance and organizational goals. These findings affirm that performance management is not only a monitoring mechanism but also a strategic instrument in the continuous development of employees.